Ultimate capacity and reinforcement area requirement for bridge girder using various FRP re-bars - Fayyadh, M.M.; Razak, Hashim Abdul; Akib, S. (Academic Journals, 2010)
An analytical study on the use of various types of fibre reinforced plastic rebars as reinforcement is presented in this paper. The structural element examined was a girder, which formed a bridge deck and was designed in accordance to the ACI code. Three types of fibres were considered in the reinforced plastic rebar, namely glass, aramid and carbon. A finite element model of the bridge girder was created using solid brick and embedded bar elements. A non-linear, three-dimensional analysis was performed to determine the deflections and stresses under an applied concentrated point load. The results revealed that the load capacity of the girder increased when fibre reinforced polymer (FRP) with same area as steel bars was used and the increase was related to the type of fibres used. Consequently, the reinforcement area required to attain a specified load capacity decreased when FRP was substituted for normal steel rebar Â© 2010 Academic Journals.